Hysteroscopic metroplasty for the treatment of the dysmorphic uterus: A SWOT analysis - Carrera, Maria; Alonso, Luis; Domínguez, Jose Antonio; Alcázar, Juan Luis; Carugno, Jose; Moratalla, Enrique; Pérez Milán, Federico; Caballero, Miguel (Frontiers in Surgery, 2023)
Introduction: Dysmorphic uterus or T-shaped uterus is an increasingly frequent diagnosis among the infertile population that has been associated to worse reproductive results. Hysteroscopic metroplasty is a safe and simple procedure that can improve the reproductive outcomes in this group of patients, although the benefits of this procedure remains controversial due to the lack of adequate scientific evidence. Objective: To analyze the hysteroscopic metroplasty using the SWOT (Strengths, Weaknesses, Opportunities and Threats) methodology. Data sources: An electronic search from inception each database up to December 2021 including the following databases was conducted: PubMed-MEDLINE, EMBASE, Web of Science, The Cochrane Library, and Google Scholar. Methods of study selection: Studies reporting outcomes of patients undergoing hysteroscopic metroplasty were included. Tabulation: Not applicable Integration and Results: Clinical evidence from the included studies suggests an improvement in reproductive results after performing hysteroscopic metroplasty especially in women with recurrent pregnancy loss and previous infertility, but all of them have relevant methodological limitations. For this reason, benefits, risks and alternatives of this intervention should be considered with caution. Conclusions: Evidence from published data shows a probable association between dysmorphic uterus and poor reproductive outcomes. Hysteroscopic metroplasty in patients with dysmorphic uterus could improve pregnancy outcomes, but there is need of properly designed prospective controlled studies to determine the benefits of this technique.